For the Rights of "Nobodies": the Globalising Tension between Human Rights and Democracy - Teraya, Koji (Victoria University of Wellington Law Review, 2007)
In this article, the author suggests that democracy should not be accepted as a wholly positive ideal without question, examining in particular the assumption that democracy always ensures the protection of human rights. To highlight this concern, the author focuses on the creation of “Nobodies” – individuals within democratic states that are expelled and, as a result, are deprived of human rights, including those who are deprived of nationality and those who are expelled by the operation of law, concluding that blind efforts to reduce “democratic deficit” may in fact aggravate the violation of Nobodies’ rights.